2020
DOI: 10.1039/d0ra08490e
|View full text |Cite
|
Sign up to set email alerts
|

Preferential N–H⋯:C hydrogen bonding involving ditopic NH-containing systems and N-heterocyclic carbenes

Abstract: Non-traditional hydrogen bonds between a singlet carbene and a series of ditopic secondary amines is detailed. Both the solid- and solution-state metrics reveal the strength of these associations are dependent on the pKa of the NH-containing molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…There are two C⋯H-C type hydrogen bonds in the crystal form of 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene (GUXJAK02) [ 118 ]. Both the dimer between 1,3-dimesityl-imidazol-2-ylidene and diphenylamine (MODVEG) [ 119 ] and between 1,3-bis[2,6- diisopropylphenyl]imidazol-2-ylidene and N ,N -diphenylbenzene-1,4-diamine (LAGYEB) [ 120 ] have one C⋯H-N hydrogen bond, while the dimer of N-methyl-2-(3-phenyl-2,3-dihydro-1H-imidazol-1-yl)ethanamine (AWIBOY) [ 121 ] has two. 1,3-dimesitylimidazol-2-ylidene in methanol (JAPDEK) [ 122 ], on the other hand, is the simplest example of the occurrence of a C⋯H-O type hydrogen bond and was reported as the first X-ray structure of a carbene–alkohol hydrogen-bonded complex.…”
Section: Resultsmentioning
confidence: 99%
“…There are two C⋯H-C type hydrogen bonds in the crystal form of 1,3-diisopropyl-4,5-dimethylimidazol-2-ylidene (GUXJAK02) [ 118 ]. Both the dimer between 1,3-dimesityl-imidazol-2-ylidene and diphenylamine (MODVEG) [ 119 ] and between 1,3-bis[2,6- diisopropylphenyl]imidazol-2-ylidene and N ,N -diphenylbenzene-1,4-diamine (LAGYEB) [ 120 ] have one C⋯H-N hydrogen bond, while the dimer of N-methyl-2-(3-phenyl-2,3-dihydro-1H-imidazol-1-yl)ethanamine (AWIBOY) [ 121 ] has two. 1,3-dimesitylimidazol-2-ylidene in methanol (JAPDEK) [ 122 ], on the other hand, is the simplest example of the occurrence of a C⋯H-O type hydrogen bond and was reported as the first X-ray structure of a carbene–alkohol hydrogen-bonded complex.…”
Section: Resultsmentioning
confidence: 99%
“…Intermolecular noncovalent interactions bear an immense technological potential owing to their versatile capability of construction of various complex supramolecular architectures which have found application in drug delivery, [1][2][3] materials engineering, 4,5 catalysis, 6,7 sensors, 6,[8][9][10] biological chemistry, [11][12][13] and many others. [14][15][16] Some prominent noncovalent interactions includes hydrogen bonding (HB), [17][18][19][20][21][22] halogen bonding (XB), 23,24 π-π interaction, [25][26][27] metal ion coordination, [28][29][30][31] hydrophobic interaction, [32][33][34][35] donor-acceptor interaction, [36][37][38] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] The pNHCs have attracted significant attention over the classical NHCs due to the existence of a proton-responsive NH group, allowing H-bonding interactions, β-deprotonations, and nucleophilic additions. [21][22][23][24][25] Kuwata and Ikariya reported that a pNHC Ru complex catalyzes the dehydrative coupling of an N-heterocycle with allyl alcohol. 26 Grotjahn and coworkers revealed that Rh and Ir complexes with pNHC ligands were effective catalysts for the transfer hydrogenation (TH) of acetophenone and chalcone.…”
Section: Introductionmentioning
confidence: 99%